Energetic Electron Precipitation Associated With Pulsating Aurora Observed by VLF Radio Propagation During the Recovery Phase of a Substorm on 27 March 2017. Issue 23 (2nd December 2018) - Tsuchiya, F.; Hirai, A.; Obara, T.; Misawa, H.; Kurita, S.; Miyoshi, Y.; Shiokawa, K.; Connors, M.; Ozaki, M.; Kasahara, Y.; Kumamoto, A.; Kasaba, Y.; et al.
Abstract: Recent studies suggest that electrons with energies up to several hundred keV precipitate into the atmosphere associated with pulsating aurora (PsA). It is debated the highest energy of precipitating electrons associated with PsA. Here we report for the first time that the energy extends to relativistic energies. PsA was observed by THEMIS all‐sky imagers during a substorm that occurred on 27 March 2017. Energetic electron precipitation was detected by very low frequency subionospheric propagation. We found similar time variations between the auroral intensity and perturbation of the received radio signal intensity when the PsA occurred on the radio path. The perturbation showed a short recovery time of 2 s. The recovery time indicates relaxation from ionospheric modification due to energetic electron precipitation and depends on the stopping altitude of the electrons. The recovery time required a stopping altitude of 50–60 km and indicates that the PsA is accompanied by relativistic electron precipitation. Plain Language Summary: Auroral patches frequently show periodic variations in brightness with periods from a few to a few tens of seconds. They are called pulsating auroras. Recent studies showed that pulsating auroras are caused by the scattering of auroral electrons by electric and magnetic waves in near‐Earth space. Theoretical studies predicted that not only the auroral electrons but very high‐energy electrons in radiation belts are scattered by the waves and precipitate into the atmosphere. To visualize the high‐energy electron precipitation, we used the ground‐based observation of man‐made very low‐frequency radio signals. We found, for the first time, that pulsations of the high‐energy electron precipitation are associated with the pulsating aurora. Because the very low frequency radio signal can propagate at long distances reflected between the ground and the lower edge of the ionosphere, radio broadcasts were used to adjust our watch, submarine communication, and so on. When the electron precipitations occur above a radio propagation path, they cause ionization in the lower ionosphere and modulation in the received radio signal. They can also contribute to a loss of the outer radiation belt during magnetic storms and have an impact on the chemistry of the middle atmosphere. Key Points: Energetic electron precipitation was observed with subionospheric VLF propagation during a substorm on 27 March 2017 Similar time variations between the pulsating aurora and energetic electron precipitation were found The short recovery time of the subionospheric perturbation indicates that pulsating aurora accompanied relativistic electron precipitation